Analisis Kepuasan Mahasiswa Universitas Muhammadiyah Pontianak Terhadap Produk Tabungan Syariah Mandiri Pada Bank Syariah Mandiri (BSM) Cabang Pontianak - Devi Yasmin; Khalid Muhajir (Universitas Muhammadiyah Pontianak, 2014)
The purpose of this study was to determine the level of satisfaction of the students at the University of Muhammadiyah Pontianak Savings products Syariah Mandiri Bank Syariah Mandiri (BSM) Branch Pontianak. This study is a descriptive study, with the entire student population of the University of Muhammadiyah Pontianak ever open a savings account at Bank Syariah Mandiri Syariah Mandiri (BSM) Pontianak in 2013 was 2,225 people. Sampling using purposive sampling, which each faculty will be represented by 20 respondents, so the total respondents were 120 people. Data were collected through questionnaires and documents of the company. Research variable is the variable quality of service consisting of reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy), and tangibles (physical evidence / real). Analyzer used in this research is importance performance analysis using Cartesian diagram. The results of this study indicate level of the average consumer satisfaction obtained X = 4.73 and the average rate of interest is Y = 4.07 which means that the average level of customer satisfaction is above the level of importance so overall the respondents are satisfied with the quality of service services provided by the Bank Syariah Mandiri Branch Pontianak. While the overall attributes associated with the fifth dimension is defined satisfaction level is above derive maximum satisfaction level, which is satisfied, except for some attributes such as queuing system at Bank Syariah Mandiri regular and attributes There are a large parking area and regularly at Bank Syariah Mandiri.